2007
DOI: 10.4012/dmj.26.924
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Modification on the Photocatalysis of Ti-Ni Alloy in Orthodontics

Abstract: Photocatalytic activity from the reaction of titanium oxide with ultraviolet light has recently gained much attention. In particular, there is scientific interest in inducing photocatalytic reactions on Ti-Ni alloy, a material widely used in orthodontic applications. However, it is believed that inducing a photocatalytic reaction with an amorphous oxide film on the alloy is a difficult challenge. In this study, therefore, we sought to induce a photocatalytic reaction on Ti-Ni alloy by subjecting the latter to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 19 publications
0
16
0
1
Order By: Relevance
“…Although UVA has a lower impact on humans than does UVB or UVC, long-term exposure to UVA can be harmful. 23 Therefore, for clinical applications, outdoor UV or UVA lamps at an intensity of 1 mW/cm 2,24 or the development of a visible light photocatalyst that reacts in indoor light is advisable. 24 In addition to studies undertaken to explore limitations in its light source, studies of the intraoral environment should be conducted to clarify fully the photocatalytic antibacterial effect and its potential clinical applications in the orthodontic field.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although UVA has a lower impact on humans than does UVB or UVC, long-term exposure to UVA can be harmful. 23 Therefore, for clinical applications, outdoor UV or UVA lamps at an intensity of 1 mW/cm 2,24 or the development of a visible light photocatalyst that reacts in indoor light is advisable. 24 In addition to studies undertaken to explore limitations in its light source, studies of the intraoral environment should be conducted to clarify fully the photocatalytic antibacterial effect and its potential clinical applications in the orthodontic field.…”
Section: Discussionmentioning
confidence: 99%
“…The surface oxide film on Ti alloys generally exists in an amorphous state, which does not indicate photocatalytic activity. 2,3 However, three crystal structures of TiO 2 -anatase, rutile, and brookite-can be produced by various oxidation methods to induce a photocatalytic reaction. 2,3 Hydroxyl radicals that are extremely reactive to organic compounds are produced by the irradiation of TiO 2 at wavelengths Ͼ385 nm, resulting in photocatalytic antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Horiuchi et al [85] modified the surface of TiNi substrates through an electrolytic treatment to thicken the oxide film followed by heat treatment to induce crystallization of the oxide surface film in order to examine antibacterial effect. The amorphous oxide film was successfully modified.…”
Section: Surface Modificationmentioning
confidence: 99%
“…Despite the reports of some authors 3,4 of the lack of cytotoxicity of alloys, a study conducted by Fili 5 found that Ni-rich precipitates in NiTi osseous implants chemically passivized with HF, HNO 3 and H 2 O 300 days after implantation. A number of methodologies were proposed with the objective of creating a barrier that would block the release of nickel, resulting in an increased biocompatibility of the alloy and corrosion resistance: anodization 6,7 , heat treatments for superficial oxidation 8,9 , sputtering 10,11 , plasma electrolytic oxidation 12 , plasma immersion ion implantation 13 , hydroxiapatite/zirconia composite coating 14 , TiN coating 15 , sol-gel technology 16 metal vapor vaccum arc plasma source 17 . The correlation of the results from these studies in regards to the corrosion resistance is complex due to the different simulated body fluids that were used as electrolytes.…”
Section: Introductionmentioning
confidence: 99%